Association Between Maternal Factors and Neonate Anthropometry: A Retrospective Cross-Sectional Study - Has, Eka Mishbahatul Mar’ah; Nursalam, Nursalam; Arief, Yuni Sufyanti (STRADA : Jurnal Ilmiah Kesehatan, 2021)
Mother’s nutritional status during pregnancy can affect fetal growth and development. This study was aimed to analyse the association between maternal factors and neonate anthropometry. This retrospective cross-sectional study involved 155 mothers of 12-23 months old children, who lived in Surabaya City, Indonesia. The independent variables were the mother’s nutritional behaviour, food belief, BMI, ANC visits, educational level, and monthly income. While the dependent were neonate’s birth weight and length. Data were gathered from questionnaire and MCH Handbook. Data were analysed using chi-square (P<0.05). Mother’s body mass index (p=0.003; C=0.235), antenatal care visits (p=0.014; C=0.193), and educational level (p=0.048; C=0.241) were associated with neonate’s birth weight. Mother’s monthly income associated with neonate’s birth length (p=0.022; C=0.181). Mother’s condition during pregnancy correlated with neonate anthropometry. Health promotion to promote regular antenatal care visits were needed to ensure mothers’ nutrition, to support optimal fetal development.